Некоторые патохимические механизмы развития гемической гипоксии у больных раком желудка - Бакурова, Е.М.; Миронова, К.А.; Зуйков, С.А.; Верхова, О.А. (Таврический медико-биологический вестник, 2012)
Розвиток тканинної гіпоксії – фактора патогенезу раку шлунку, може бути обумовлений порушенням газопостачальної функції еритроцитів. Їх дисметаболічні процеси - підвищення продукції активних форм кисню, оксиду азоту, зниження активності глутатіонпероксидази, глюкозо-6-фосфатдегідрогенази, підвищення активності гліколітичних ферментів – гліцеральдегід-3-фосфатдегідрогенази і лактатдегідрогенази, можуть безпосередньо впливати на порушення транспорту кисню в тканині. The development of tissue hypoxia is a pathogenic factor of stomach cancer. It can be conditioned by disorder of gas-transport function of red cells. Erythrocytes dysfunction can be caused by their dysmetabolic processes. At this study we revealed that erythrocytes dysfunction may be due to hyperproduction of nitrogen oxide and oxygen active forms, increased activities of glycolytic enzymes and decreased activities of glutathione peroxidase, glucose-6-phosphate dehydrogenase.